Extending healthcare's reach. - Moore, S.K.
Telemedicine, or treating patients from afar, promises to alter the medical landscape. Technological solutions are being implemented that can spread critical medical expertise across a region and around the globe. For example, a U.S. company believes that the shortage of physicians specializing in intensive care can be mitigated by its telemedicine system. The performance of transatlantic surgery by remote control proved that, with the right equipment, surgeons can perform and teach advanced procedures from thousands of kilometers away. Finally, in the nations and territories of the Pacific Rim, healthcare information networks are granting the regions widely scattered citizens new access to medical expertise
Keywords: Centralized care management; Decision support system; Healthcare information networks; Intensive care; Military medicine; Professional guardrails; Remote control; Surgical globe-trotter.; Telemedicine; Transatlantic surgery